Global trends in microelectronics and place of Belarus in this process - Belous, A. I.; Pilipenko, V. A.; Turtsevich, A. S.; Shvedov, S. V. (Technology and design in electronic equipment, 2012)
The review summarizes development of microelectronics in the developed countries over the period of 7–10 years until 2008, when the economic crisis started to effect the global economy. The data from Stat World Fab Watch has been used in the paper. Achievements and potential of "Integral" PC — the parent organization responsible for the microelectronic industry in Belarus — are also reviewed.